Post COVID and Apheresis – Where are we Standing? - Steenblock, Charlotte; Walther, Romy; Tselmin, Sergey; Jarzebska, Natalia; Voit-Bak, Karin; Toepfner, Nicole; Siepmann, Timo; Passauer, Jens; Hugo, Christian; Wintermann, Gloria; Julius, Ulrich; Barbir, Mahmoud; Khan, Tina Z.; Puhan, Milo A.; Straube, Richard; Hohenstein, Bernd; Bornstein, Stefan R.; Rodionov, Roman N. (Hormone and Metabolic Research, 2022)
A continual increase in cases of Long/Post COVID constitutes a medical and socioeconomic challenge to health systems around the globe. While the true extent of this problem cannot yet be fully evaluated, recent data suggest that up to 20% of people with confirmed SARS-CoV-2 suffer from clinically relevant symptoms of Long/Post COVID several weeks to months after the acute phase. The clinical presentation is highly variable with the main symptoms being chronic fatigue, dyspnea, and cognitive symptoms. Extracorporeal apheresis has been suggested to alleviate symptoms of Post/COVID. Thus, numerous patients are currently treated with apheresis. However, at present there is no data from randomized controlled trials available to confirm the efficacy. Therefore, physicians rely on the experience of practitioners and centers performing this treatment. Here, we summarize clinical experience on extracorporeal apheresis in patients with Post/COVID from centers across Germany.
Keywords: long COVID; post COVID; apheresis; fatigue; autoantibodies; Immunity